A seven-year single-center experience on AngioJet rheolytic thrombectomy in patients with pulmonary embolism at high risk and intermediate-high risk - Akbal, Ozgur Yasar; Keskin, Berhan; Tokgoz, Hacer Ceren; Hakgor, Aykun; Karagoz, Ali; Tanyeri, Seda; Kaymaz, Cihangir (Kare Publ, 2021)
Objective: AngioJet rheolytic thrombectomy (ART) has been used as a catheter-based treatment for acute pulmonary embolism (PE). In this study, based on our 7-year experience with ART in patients with PE, we evaluated the efficacy and safety outcomes of ART. Methods: Our study is based on retrospective evaluation of 56 patients with high- and intermediate-high-risk PE, with an average age of 62 years [interquartile range (IQR) 50-73 years] who underwent ART. Results: High and intermediate-high risks were noted in 21.4% and 78.6% of the patients, respectively. The ART duration was 304 (IQR: 246-468) seconds. Measures of obstruction, right to left ventricle diameter ratio, right to left atrial diameter ratio, and pulmonary arterial pressures were improved (p<0.001 for all). During the hospital stay, acute renal failure, major and minor bleeding, and mortality rates were 37.5%, 7.1%, 12.5%, and 8.9%, respectively. Aging related to post-procedural nephropathy while high-risk status was associated with in-hospital mortality (p=0.006) and long-term mortality. Conclusion: ART resulted in significant and clinically relevant improvements in the pulmonary arterial thrombotic burden, right ventricle strain, and hemodynamics in patients with PE at high and intermediate-high risk. Aging increased the risk of post-procedural nephropathy, whereas baseline high-risk status predicted in-hospital and long-term mortality.
Keywords: pulmonary embolism; thrombectomy; mechanical thrombolysis; angioJet rheolytic thrombectomy